Advance care planning readiness for Chinese older people: An integrative review and conceptual framework - Wong Kalok; Yuan Hao-Bin; Kunaviktikul Wipada (Sciendo, 2023)
Advance care planning is a process of discussion in which patients can communicate their end-of-life care preferences to family members and health care providers for consideration. Readiness for advance care planning is a patient's preparedness to engage in advance care planning. This review aims to develop the conceptual framework for advance care planning readiness for Chinese older people. The current knowledge from the published studies was identified and synthesized by an integrative review. The conceptual framework was developed based on the social-ecological model and the theory of planned behavior. The factors from the social environment/community, health care professionals, and individual/family layers were defined. These factors may influence an individual's medical decision-making, which in turn triggers individual behavioral mechanisms that arise from interactions between motivations, attitudes, and beliefs. Relevant factors should be considered when assessing the behavior of personnel engaged in advance care planning or formulating appropriate intervention measures to improve advance care planning participation in China. This framework can be used to guide studies that explore how the social/familial/individual factors predict the readiness for advance care planning among Chinese older people, and to design intervention studies to test the effect of family function on the readiness for advance care planning.